1978
DOI: 10.1093/infdis/138.2.252
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Subtypes of Hepatitis B Surface Antigen with e Antigen and Its Corresponding Antibody

Abstract: A total of 3,212 samples of blood from asymptomatic volunteer donors positive for hepatitis B surface antigen (HBsAg) by radioimmunoassay and 860 samples negative for HBsAg were tested for the presence of hepatitis e antigen (HBeAg) and its corresponding antibody (anti-HBe) using a rheophoresis technique. Neither HBeAg nor anti-HBe was detected in any sample negative for HBsAg. Of the HBsAg-positive samples, 237 (7.4%) contained HBeAg and 749 (23.3%) had anti-HBe. HBeAg was significantly (P less than or equal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

1978
1978
1995
1995

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
3
2
0
Order By: Relevance
“…In previous studies, an associa tion between HBeAg or its antibody and an antigenic marker of HBsAg has been re ported [7,22], We have confirmed the ob servation of Nath et al [22] of an associa tion of anti-HBe with the d determinant and the observation of Couroucé-Pauty and Plançon [7] of an excess of HBeAg in asso ciation with the r determinant. However, among the samples analyzed in the present study, 8 of the 15 r+ HBeAg-positive sam ples were from preteen and teen-aged chil dren in the Solomon Islands.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In previous studies, an associa tion between HBeAg or its antibody and an antigenic marker of HBsAg has been re ported [7,22], We have confirmed the ob servation of Nath et al [22] of an associa tion of anti-HBe with the d determinant and the observation of Couroucé-Pauty and Plançon [7] of an excess of HBeAg in asso ciation with the r determinant. However, among the samples analyzed in the present study, 8 of the 15 r+ HBeAg-positive sam ples were from preteen and teen-aged chil dren in the Solomon Islands.…”
Section: Discussionsupporting
confidence: 85%
“…Thus, the asso ciation noted in our samples may be one of HBeAg with the age of the carrier [24] and not with a particular antigenic marker of HBsAg. In addition, we found an associa tion of HBeAg with the l determinant and possibly of anti-HBe with the absence of l. In a larger study of antigen specimens from the United States Red Cross donor popula tion, an association of HBeAg with the y determinant was reported [22], Couroucé-Pauty and Plançon [7] noted that HBeAg and anti-HBe were more prevalent in ad type antigens. Among the samples analyzed in the present study, 54.8% of ad and 46.3% of ay samples contained either HBeAg or anti-HBe (x2 = 1.38).…”
Section: Discussionsupporting
confidence: 50%
“…Nath et al [ 19781 studied sera from American HBsAg-positive blood donors using a hemagglutination method for HBV subtyping and rheophoresis (a modification of the immunodiffusion method) for HBeAg/anti-HBe testing. While they also found that anti-HBe was more prevalent among ad than ay carriers, they observed, in contrast to Courouci-Pauty and Plancon's [ 19781 findings, that HBeAg was significantly more common in ay than ad carriers [Nath et al, 1978]. * In the present study, in which both HBeAg/anti-HBe and HBV subtype were determined by RIA, the association of adw2 with anti-HBe was again found, as was the association of the major y-type virus (ayw3) with HBeAg as reported by Nath et al [1978].…”
Section: Discussionsupporting
confidence: 78%
“…There is a considerable body of published studies from areas of the world where both adw2 and ayw3 strains of HBV are prevalent, suggesting that ay infections predominate among patients with acute type B hepatitis, while ad infections are more common among chronic HBV carriers, with or without liver disease [Holland et al, *We suggest the possibility that the approach taken by Nath et al [1978] led to the exclusion of all uyw2-type sera. Our experience (unpublished) has been that if one immunizes an animal with serum containing HBV/udw2, a viral strain which bears both the dand g antigenic determinants, the antiserum produced can be expected to contain both anti-d and anti-g, as well as anti-a.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation